2022
DOI: 10.3389/fendo.2022.903731
|View full text |Cite
|
Sign up to set email alerts
|

Non-Alcoholic Fatty Liver Disease (NAFLD) Is an Independent Risk Factor for Developing New-Onset Diabetes After Acute Pancreatitis: A Multicenter Retrospective Cohort Study in Chinese Population

Abstract: BackgroundNumerous studies validated frequent glucose dysfunction in patients with acute pancreatitis (AP). However, the prevalence of new-onset diabetes in individuals after a first episode of AP varies widely among previous studies. This study aims to determine the incidence of post-acute pancreatitis diabetes mellitus (PPDM-A) in Chinese people and further identify potential risk factors that influence diabetes development in patients with AP.MethodsThis was a multi-center retrospective cohort study includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 53 publications
1
6
1
Order By: Relevance
“…We found no association between new-onset DM and hypertension ( 20 , 36 , 37 , 43 ), cardiovascular disease ( 20 , 36–38 , 43 ), or age ( 20 , 38 , 43 ). Smoking ( 29 , 31 , 36–38 , 43 , 64–66 ), alcohol consumption ( 29 , 31 , 36 , 37 , 64 , 67 ), and male sex ( 20 , 27 , 31–33 , 35–38 , 41 , 42 , 47 , 50 , 61 , 62 , 68–70 ) were not associated with either new-onset DM or PD/DM.…”
Section: Resultscontrasting
confidence: 64%
See 3 more Smart Citations
“…We found no association between new-onset DM and hypertension ( 20 , 36 , 37 , 43 ), cardiovascular disease ( 20 , 36–38 , 43 ), or age ( 20 , 38 , 43 ). Smoking ( 29 , 31 , 36–38 , 43 , 64–66 ), alcohol consumption ( 29 , 31 , 36 , 37 , 64 , 67 ), and male sex ( 20 , 27 , 31–33 , 35–38 , 41 , 42 , 47 , 50 , 61 , 62 , 68–70 ) were not associated with either new-onset DM or PD/DM.…”
Section: Resultscontrasting
confidence: 64%
“…We found that obesity ( 29 , 39 , 41 , 43 , 49 , 50 , 62 ) and chronic kidney disease ( 36 , 38 , 43 ) were associated with a significantly higher odds of developing DM (OR: 1.85; CI: 1.43–2.38 and OR: 2.10; CI: 1.85–2.38, respectively). We observed a statistically non-significant tendency of increased odds of developing DM with liver cirrhosis ( 20 , 38 , 63 ), other liver disease ( 37 , 43 , 64 ), dyslipidemia ( 20 , 37 , 42 , 43 ), and being overweight or obese ( 37 , 41 , 50 ). We found no association between new-onset DM and hypertension ( 20 , 36 , 37 , 43 ), cardiovascular disease ( 20 , 36–38 , 43 ), or age ( 20 , 38 , 43 ).…”
Section: Resultsmentioning
confidence: 69%
See 2 more Smart Citations
“…The potential explanation is that this particular population has an underlying predisposition toward T2DM and the additional insult of AP accelerates the progression to sustained hyperglycemia[ 21 , 22 ]. In another study, Lv et al [ 23 ] found similar results but also discovered non-alcoholic fatty liver disease (NAFLD) was an additional independent risk factor. Until now, most studies have focused on the effect of the exocrine pancreas on endocrine function yet the liver also plays a critical role in regulating and maintaining glucose levels.…”
Section: Risk Factorsmentioning
confidence: 72%